CCUS National Research Agenda Portugal - Dos-Santos, M.J.P.L.; Bacariza, C. (2026)
Portugal has set ambitious GHG emission reduction targets underthe Climate Framework Law (Law No. 98/2021) and the NationalEnergy and Climate Plan (NECP). By 2030, the country aims for atleast a 55% reduction in total greenhouse gas emissions comparedto 2005 levels, in line with the EU Effort Sharing Regulation. Thistarget supports the EU-wide 2030 goals and is backed by specificpolicies on renewables, energy efficiency, and sectorial measures.For the longer term, Portugal targets climate neutrality (net-zero) by2050, with a gross emissions reduction of around 90% versus 2005,complemented by carbon removals (mainly through LULUCF sinks).An intermediate target of 65–75% reduction is established for 2040.Some strategic documents also mention advancing neutrality toward2045. These goals are enshrined in national law and regularlyupdated in official NECP reports. (PDF) TECHNO-ECONOMIC ANALYSIS OF CARBON MITIGATION TECHNOLOGIES CA21127 CCUS National Research Agenda Country: Portugal Contributor and Institution/Affiliation. Available from: https://www.researchgate.net/publication/405595381_TECHNO-ECONOMIC_ANALYSIS_OF_CARBON_MITIGATION_TECHNOLOGIES_CA21127_CCUS_National_Research_Agenda_Country_Portugal_Contributor_and_InstitutionAffiliation?channel=doi&linkId=6a1d50b6199152051ec01917&showFulltext=true [accessed Jun 01 2026].